2019
DOI: 10.1002/tox.22842
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of trehalose against Mn‐induced α‐synuclein oligomerization in mice: Involvement of oxidative stress and autophagy

Abstract: Overexposure to manganese (Mn) is widely known to induce alpha-synuclein (α-Syn) oligomerization, which has been attributed to the oxidative damage of α-Syn protein.Trehalose has been shown to induce autophagy and serve as a chemical chaperone, but little information has been reported about its effect on Mn-induced α-Syn oligomerization. In this study, we investigate whether trehalose can effectively interfere with Mn-induced α-Syn oligomerization, using different concentrations of trehalose (2% and 4% (g/vol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The result obtained appears to differ from some previous findings. In particular, treatment with 2% and 4% trehalose solution similarly enhanced autophagy in the brain tissue in a mouse model of Mn-induced α-synuclein oligomerization [ 23 ]. In rats, treatment with 2% and 5% trehalose solution had similar effects on autophagy induction in the brain, while 0.5% solution was ineffective in a AAV1/2-based rat model of Parkinson’s disease [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result obtained appears to differ from some previous findings. In particular, treatment with 2% and 4% trehalose solution similarly enhanced autophagy in the brain tissue in a mouse model of Mn-induced α-synuclein oligomerization [ 23 ]. In rats, treatment with 2% and 5% trehalose solution had similar effects on autophagy induction in the brain, while 0.5% solution was ineffective in a AAV1/2-based rat model of Parkinson’s disease [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The safety of taking high doses of trehalose [ 15 , 16 ], the efficiency of the oral and parenteral administration of the drug [ 17 ], the dose dependence of the therapeutic effect of the drug [ 18 ], the effects of continuous treatment [ 13 , 17 ] or intermittent regimen [ 19 ], as well as the age-dependence, [ 13 ] have been researched. The studied concentrations of trehalose solution in the diet range from 1% to 5%, with different amplitudes of the achieved autophagic response [ 18 , 20 , 21 , 22 , 23 ]. A 2% concentration of trehalose in the drinking water is considered standard to induce neuroprotective effects in laboratory rodents [ 18 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Trehalose is a disaccharide comprised of two glucose molecules which is synthesized in bacteria, fungi, plants, and invertebrate animals. Trehalose has been shown to afford protective effects against Mn-induced neurotoxicity in the murine brain by increasing autophagy activation along with attenuation of Mn-induced oxidative stress and α-Syn oligomerization ( Jing et al, 2020 ). Trehalose mitigated Mn-induced PINK1/parkin-dependent mitophagy dysregulation by attenuating Mn-increased cleaved-poly (ADP-ribose) polymerase (PARP) and mitochondria-containing autophagic lysosomes, resulting in inhibition of Mn-induced mitochondrial damage and apoptosis in mice ( Liu et al, 2019 ).…”
Section: Neurotherapeutics and Their Potential Underlying Mechanisms ...mentioning
confidence: 99%
“…Several compounds such as estrogens and riluzole attenuated Mn-induced glutamatergic excitotoxic neuronal injury by upregulating astrocytic glutamate transporters such as excitatory amino acid transporter 1 (EAAT1) and EAAT2 [glutamate-aspartate transporter (GLAST) and glutamate transporter 1 (GLT-1) in rodents, respectively] ( Fumagalli et al, 2008 ; Lee et al, 2009a ). A disaccharide trehalose attenuated Mn-induced neurotoxicity by modulating Mn-impaired autophagy and mitophagy ( Liu et al, 2019 ; Jing et al, 2020 ). Chelating agents such as ethylenediaminetetraacetic acid (EDTA) ( Discalzi et al, 2000 ) and para-aminosalicylic acid (PAS) have been shown to reduce acute Mn toxicity by promoting Mn excretion from the body ( Jiang et al, 2006 ; Zheng et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%